The Irreconcilable Conflict between Islam and Liberalism - Siddique, Muhammad Zahid (Islamic Studies, 2021)
John Rawls used an apparently neutral apparatus to derive the principles of justice that all “rational” people ought to agree with because they provide the basis of coexistence in a pluralistic society. He believes that religious faith is consistent with the commitment to liberalism. The paper shows that the Rawlsian liberal “self” modelled in the original position is not consistent with the original position recognized by religion in general and Islam in particular. According to Islam, the human self is mukallaf (subject of God) while Rawls treats it non-mukallaf. This is so because Rawlsian original position presumes an atheist self behind the veil of ignorance. This conceptualization of self is not only inconsistent with but also hostile to religion. The claims about liberalism’s tolerance towards religion are superficial. The liberal self can express itself in various religious forms provided these are aligned with the system of rights acknowledged by the liberal atheist self.